C and Python applications embedding Python code in C programs, SQL methods, and Python sockets - Joyce, Philip (Software engineer) (Apress, 2022)
Solve problems by embedding Python code in a C programs, SQL methods, Python sockets. This book uses rudimentary mathematics and basic programming to create practical Python applications for embedding. You'll start with an introduction to C and Python, assuming a fundamental understanding of what programming is. You will also review the basics of the database management language, SQL. You will learn how to use SQL from a C program and from a Python program. C and Python have different programming strengths, and you will learn how to write a Python program embedded within a C program to profit from the strength of each, in one program. Finally, you will explore how socket programs enable two computers to communicate with each other. Here the book covers basic server-client, basic threaded, and basic chat programs. You will: Review basic Python and C coding Understand the methods of embedding Python code within a C program Create typical programs in Python and C using SDK Work with socket applications in Python.